2022
DOI: 10.1002/anie.202200994
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biosynthesis of the [Fe]‐Hydrogenase Cofactor Verifies the Proposed Biosynthetic Precursors

Abstract: In the FeGP cofactor of [Fe]‐hydrogenase, low‐spin FeII is in complex with two CO ligands and a pyridinol derivative; the latter ligates the iron with a 6‐acylmethyl substituent and the pyridinol nitrogen. A guanylylpyridinol derivative, 6‐carboxymethyl‐3,5‐dimethyl‐4‐guanylyl‐2‐pyridinol (3), is produced by the decomposition of the FeGP cofactor under irradiation with UV‐A/blue light and is also postulated to be a precursor of FeGP cofactor biosynthesis. HcgC and HcgB catalyze consecutive biosynthesis steps l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 45 publications
(1 reference statement)
1
44
0
Order By: Relevance
“…5 This homodimeric enzyme contains one non-redox active iron per subunit linked to a guanylylpyridinol cofactor 27 in short the FeGP cofactor. 90 The biosynthesis of FeGP has not yet been fully elucidated. So far, it is known that 2-(4,6-dihydroxy-3,5-dimethylpyridin-2yl)acetic acid 75 is the biosynthetic precursor for FeGP 27, while so far only a few preliminary feeding experiments with 13 C-labeled building blocks such as acetic acid and pyruvate could give some clues about the origin of the pyridine ligand.…”
Section: Coenzymes Of Methanogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…5 This homodimeric enzyme contains one non-redox active iron per subunit linked to a guanylylpyridinol cofactor 27 in short the FeGP cofactor. 90 The biosynthesis of FeGP has not yet been fully elucidated. So far, it is known that 2-(4,6-dihydroxy-3,5-dimethylpyridin-2yl)acetic acid 75 is the biosynthetic precursor for FeGP 27, while so far only a few preliminary feeding experiments with 13 C-labeled building blocks such as acetic acid and pyruvate could give some clues about the origin of the pyridine ligand.…”
Section: Coenzymes Of Methanogenesismentioning
confidence: 99%
“…So far, it is known that 2-(4,6-dihydroxy-3,5-dimethylpyridin-2yl)acetic acid 75 is the biosynthetic precursor for FeGP 27, while so far only a few preliminary feeding experiments with 13 C-labeled building blocks such as acetic acid and pyruvate could give some clues about the origin of the pyridine ligand. 90 3. Can the analysis provide insight into coenzyme evolution?…”
Section: Coenzymes Of Methanogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed biosynthesis pathway of the FeGP cofactor. [11,[24][25][26][27][28][29] Chemistry-A European Journal which the distance could be shortened to ~3.8 Å. [33] Thus, open/closed conformation changes were proposed as the required step for H À transfer.…”
Section: Catalytic Mechanism Of [Fe]-hydrogenasementioning
confidence: 99%
“…HcgA and HcgG may be SAM‐dependent enzymes, but their real functions are unknown [28] . A recent report showed that the FeGP cofactor can be synthesized in vitro using synthetic ligand precursors, Fe, CO, H 2 and cell extracts from Methanococcus maripaludis ΔhcgBΔhcgC , HcgB and HcgC enzymes [29] …”
Section: Biosynthesis Of the Fegp Cofactormentioning
confidence: 99%